The Determinants Factors of Capital Expenditure - Jouzar Farouq Ishak; Yeni Priatna Sari; Yevi Dwitayanti; Hasbi Assidiki Mauluddi (Yayasan Ilomata, 2021)
This study examines the determinant factors of capital expenditure government, through local own-source revenue, revenue sharing fund, general allocation fund, and special allocation fund. The data was collected from 23 provincial government in Indonesia. The method used is multiple regression in provincial government in 2010-2019. The regression results support all hypotheses, but not the fourth hypothesis. This study shows that provincial government can not to be autonomous and need funding from central government. This study offers a robust link between local own-source revenue and balance fund by examining how their interaction produces a variation in the level of capital expenditure.